Micro-Loans and Household Economies: Evidence in Indonesia - S. Suratini (Signifikan: Jurnal Ilmu Ekonomi, 2018)
Micro-loans intended to improve household economies are a fascinating subject for research because a comparative analysis of before and after taking micro-loans would result in a bias selection. Households have different prior conditions from one another, so the difference found during the study is not entirely due to receiving micro-loans. There is a risk of moral hazard risk due to asymmetric information. This research adopts the double difference (DD) fixed effects method to estimate the extent of micro-loans’ impact. Results indicate that micro-loans are significantly influencing the household economies. The impact size was relatively small that it was not apparent during regression. As an implication, micro-loans intended for productive purposes can help improve household economic conditions. Effective and sustainable monitoring and counsel can minimize the risk of moral hazard.DOI: 10.15408/sjie.v7i1.5954